Effect of interferon treatment on glucose metabolism in children with chronic hepatitis B infection - Zarife KULOĞLU; Aydan KANSU; Merih BERBEROĞLU; Fulya G. DEMİRÇEKEN and Gönül ÖCAL and Nurten GİRGİN (Turkish Journal of Gastroenterology, 2019)
-